The great Irish (de)leveraging 2005-14 - Reamonn Lydon; Tara McIndoe-Calder (European Central Bank (ECB), 2017)
Drawing on the 2013 Household Finance and Consumption Survey (HFCS) and complementary administrative data sources, we simulate household balance sheets at the micro level for the 2005-14 period. We use this dataset to tell the story of household leveraging and deleveraging over a tumultuous period for the Irish economy. We show that deleveraging has proceeded at a signficantly faster pace for older households, when compared with younger age groups. In contrast, we find t hat a higher-incidence of t racker mortgages amongst younger borrowers - which passed through the historically low ECB policy rates since 2009 - relative to older borrowers has played a major role in easing the debt repayment burden in the presence of large income shocks. Notwithstanding historically low interest rates, we show that income shocks are the main factor contributing to mortgage repayment problems. However, there is also a role for equity factors.
Keywords: D12; D31; E21; 330; Households; Debt; Assets; Income; Deleveraging